A climatic evaluation of the southern dispersal route during MIS 5e. (1st March 2022) - Nicholson, Samuel Luke; Hosfield, Rob; Groucutt, Huw S.; Pike, Alistair W.G.; Burns, Stephen J.; Matter, Albert; Fleitmann, Dominik
Abstract: Homo sapiens dispersals out of Africa are often linked to intensifications of the African and Indian Summer Monsoons. Current models advocate that dispersals along the "southern-route" into Arabia occurred during Glacial Termination-II (T-II), when lower sea-level and reduced Bab-al-Mandab width increased the likelihood of crossing. The precise phasing between sea-level and monsoon precipitation is thus key to assess the likelihood of a successful crossing or the behavioural and technological capacities that facilitated crossing. Based on a precisely-dated stalagmite record from Yemen, we reveal a distinct phase-lag of several thousand years between sea-level rise and major monsoon intensification. Pluvial conditions in Southern Arabia during MIS 5e lasted from ∼127.7 to ∼121.1 ka BP and occurred when sea-levels were already higher than at present. Based on our observations, we propose three models for the dispersal of H. sapiens which all have pertinent implications for our understanding of human technological and behavioural capacities during MIS 5e. Highlights: Timing of MIS 5e monsoon intensification in Southern Arabia (SAHP 4) confined to 127.7-121.1 ka BP. SAHP 4 represents the most substantial increase of rainfall in the last 130 ka BP. The onset of monsoon intensification lagged sea-level rise.